Antioxidant‐rich foods and response to altitude training: A randomized controlled trial in elite endurance athletes. (1st June 2018) - Koivisto, A. E.; Paulsen, G.; Paur, I.; Garthe, I.; Tønnessen, E.; Raastad, T.; Bastani, N. E.; Hallén, J.; Blomhoff, R.; Bøhn, S. K.
Abstract : High doses of isolated antioxidant supplements such as vitamin C and E have demonstrated the potential to blunt cellular adaptations to training. It is, however, unknown whether intake of high doses of antioxidants from foods has similar effects. Hence, the aim of the study was to investigate whether intake of antioxidant‐rich foods affects adaptations to altitude training in elite athletes. In a randomized controlled trial, 31 national team endurance athletes (23 ± 5 years) ingested antioxidant‐rich foods (n = 16) or eucaloric control foods (n = 15) daily during a 3‐week altitude training camp (2320 m). Changes from baseline to post‐altitude in hemoglobin mass (Hbmass ; optimized CO rebreathing), maximal oxygen uptake (VO2max ; n = 16) or 100 m swimming performance (n = 10), and blood parameters were compared between the groups. The antioxidant group significantly increased total intake of antioxidant‐rich foods ( 118%) compared to the control group during the intervention. The total study population improved VO2max by 2.5% (1.7 mL/kg/min, P = .006) and Hbmass by 4.7% (48 g, P < .001), but not 100 m swimming performance. No difference was found between the groups regarding changes in Hbmass, VO2max or swimming performance. However, hemoglobin concentration increased more in the antioxidant group (effect size = 0.7; P = .045) with a concomitantly larger decrease in plasma and blood volumes compared to control group. Changes in ferritin and erythropoietin from pre‐ to post‐altitude did not differ between the groups. Doubling the intake of antioxidant‐rich foods was well tolerated and did not negatively influence the adaptive response to altitude training in elite endurance athletes.